Bridge concrete cooling coating and preparation method thereof
By using bridge concrete cooling coatings prepared with water-based silicone-propylene resin and other materials, the problem of coatings in the prior art that cannot cool down at high temperatures in summer and the light reflection of composite titanium dioxide is not significant, achieving efficient solar light reflection and radiation cooling effects , improves the durability and waterproof performance of the paint.
Patent Information
- Application Number
- CN202411166058.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2024-12-20
AI Technical Summary
The existing bridge concrete waterproof coating cannot effectively cool down in high temperature weather in summer, resulting in too large temperature difference between the concrete surface and internal, causing problems such as cracks and settlement. The light reflection of composite titanium dioxide is not significantly improved and has insufficient durability.
Using aqueous silicone-propylene resin, titanium dioxide, alumina, barium sulfate, rare earth silicate, heavy calcium carbonate, calcium hydroxide, quartz sand, mica powder, talc powder, zinc phosphate and other materials, through specific mixing and dispersion processes , bridge concrete cooling coating with high solar reflectivity and radiation cooling functions is formed, and its weather resistance is enhanced by regulating the calcium carbonate structure.
It realizes the reflection of the entire band of sunlight energy by more than 94%, reduces the concrete surface temperature, prevents the shrinkage stress problem due to excessive temperature gradient, has excellent waterproofing performance and durability, and can effectively extend the service life of the bridge.
Smart Images

Figure BDA0005007916210000071 
Figure BDA0005007916210000081 
Figure BDA0005007916210000082
Abstract
Description
Technical Field
[0001] The invention belongs to the field of building materials, and particularly relates to a bridge concrete cooling coating and a preparation method thereof. Background Art
[0002] Traditional bridge concrete protective coatings only focus on waterproof performance and do not have a cooling effect. In hot summer weather, the temperature difference between the concrete surface and the interior is too large, causing the shrinkage stress to exceed the bearing capacity of the concrete, which can easily cause problems such as separation between concrete layers, damage at wide and narrow joints, and uneven settlement. In addition, current waterproof coatings mostly use materials such as polyurea with better film-forming effects. The film-forming materials may also have a certain impact on the reflective heat insulation performance. At the same time, the weather resistance, color retention, and stain resistance of the film-forming materials also affect the durability of reflective heat insulation. In addition, the organic polymers commonly used in current waterproof coatings, such as styrene acrylic emulsion and acrylic emulsion, have problems such as organic polymer coatings being easily contaminated by various organic or inorganic atmospheric pollutants due to factors such as low surface hardness, hard in winter and soft in summer, and easy generation of static electricity on the surface, which reduces the reflectivity and cannot maintain the reflective heat insulation effect for a long time.
[0003] Based on this, a bridge concrete cooling coating is provided, which has an excellent waterproof effect and can transfer the heat radiated from sunlight to the concrete surface through reflection and radiation in hot summer weather. Lowering the concrete surface temperature is currently in urgent need.
[0004] CN109593431B, the invention name "A cooling and heat-insulating protective coating for concrete bridges" discloses that the coating includes the following raw materials in parts by weight: 100 parts of liquid epoxy resin, 15-25 parts of curing agent, 8-15 parts of composite pigment, 20-40 parts of composite filler, 0.2-1 part of anti-settling agent, and 0.5-1 part of anti-cracking fiber; the liquid epoxy resin has a viscosity of 450-600cP at 25°C, an epoxy equivalent of 180-220, and a curing temperature of 5°C-10°C; the curing agent is a compound of a modified fatty amine liquid curing agent and a modified polyamide resin, the modified fatty amine liquid curing agent is a modified fatty amine resin, the modified fatty amine resin has a viscosity of 8-12cP at 25°C, and an amine value of 550-750mg KOH / g; the modified polyamide resin has a viscosity of 9-11cP at 25°C, and an amine value of 650mg KOH / g; the mass ratio of modified fatty amine resin to modified polyamide resin is 2:3-8; the composite pigment is glass microspheres, and the surface of the glass microspheres is coated with a perylene pigment coating; the refractive index of the glass microspheres is 1.80-1.95, and the particle size range is 15μm-125μm; the composite filler includes rutile nano titanium dioxide and anatase nano titanium dioxide, and the ratio of rutile nano titanium dioxide to anatase nano titanium dioxide is 1:0.4-0.8; the anti-settling agent is a titanate coupling agent; the cooling and heat-insulating protective coating for concrete bridges of the present invention can reflect sunlight, effectively reduce the surface temperature of the bridge, and increase the service life of the bridge.
[0005] This patent uses glass beads as light reflective material. Although it is a commonly used material at present, when it is applied to coatings for road and bridge concrete, the introduction of hollow glass beads increases the surface defects of the substrate, destroys its overall structure, and weakens the material in hardness and impact strength. The environment of roads and bridges is worse than that of urban buildings, and the requirements for coatings are more stringent.
[0006] CN105778569B, the invention name "A method for preparing a composite titanium dioxide powder coated with titanium light calcium carbonate" discloses that the method includes the following steps: a. dissolving butyl titanate in an organic solvent to form a butyl titanate solution; b. adding light calcium carbonate to the butyl titanate solution and uniformly dispersing it into a suspension; c. adding deionized water to the suspension at a uniform speed under stirring to hydrolyze butyl titanate, and then aging it for 10 to 20 minutes; d. introducing nitrogen into the suspension, adding methyl methacrylate under nitrogen protection, and stirring for 5 to 10 minutes; e. heating the system to 70 to 80°C, adding a small amount of initiator, and performing surface treatment for 40 to 60 minutes; f. after the surface treatment, cooling the system naturally, filtering the slurry with a Buchner funnel, washing the filter cake with deionized water, drying, and crushing. The pigment performance of the titanium dioxide product is improved, and the titanium dioxide product is surface treated to enhance its dispersion stability in organic solvents and its weather resistance. The most important thing is that the titanium dioxide used is mostly rutile titanium dioxide, which has a small electronic band gap (3.2eV), resulting in a high absorption rate of ultraviolet light. For radiation cooling coatings that require more than 90% or more, the ultraviolet light energy, which accounts for 4% of the total solar energy, is still very important. Therefore, improving its reflectivity will help improve the radiation cooling performance of the coating. However, this patent does not solve the above problems, and its application in roads and bridges may have problems such as insufficient durability and weak bonding. Summary of the invention
[0007] The purpose of the present invention is to solve the problem that the current waterproof cooling coatings, especially road and bridge coatings, have poor hardness and impact strength due to the addition of glass beads, and the current coatings prepared with composite titanium dioxide have no significant improvement in light reflection, especially no significant ultraviolet light reflection, and poor durability, and to provide a bridge concrete cooling coating and a preparation method.
[0008] The invention discloses a bridge concrete cooling paint, which is composed of 20-30 parts of water-based silicone acrylic resin, 10-20 parts of titanium dioxide, 10-20 parts of aluminum oxide, 5-10 parts of barium sulfate, 2-10 parts of rare earth silicate, 1-10 parts of heavy calcium carbonate, 1-10 parts of calcium hydroxide, 0.01-2 parts of calcium carbonate regulator, 2-10 parts of quartz sand, 1-5 parts of mica powder, 1-5 parts of talc powder, 1-5 parts of zinc phosphate, 1-5 parts of auxiliary agent, 0.5-1 part of alkaline regulator and 10-20 parts of deionized water in parts by weight;
[0009] The calcium carbonate control agent is composed of zinc sulfate, magnesium silicate and glycerol in a mass ratio of 1:1-5:1-10.
[0010] The titanium dioxide is rutile titanium dioxide.
[0011] Furthermore, the water-based silicone acrylic resin is one of the copolymer emulsions modified by organosiloxane and acrylate, and the diameter of its solid particles is 100-500nm.
[0012] Furthermore, the titanium dioxide is rutile titanium dioxide with a particle size of 250 to 800 nm.
[0013] Furthermore, the rare earth silicate is one or more of zirconium yttrium silicate, lanthanum yttrium silicate, yttrium cerium silicate, zirconium lanthanum silicate, yttrium silicate, ytterbium silicate, cerium silicate, gadolinium silicate, samarium silicate, erbium silicate, and holmium silicate.
[0014] Furthermore, the auxiliary agent is a dispersant, a defoamer, a wetting agent, a leveling agent and a thickener; the dispersant is a high molecular weight block copolymer solution containing pigment affinity groups or an aqueous solution containing a polymer with high pigment affinity groups and a surfactant, or a combination of the two; the defoamer is a polyether siloxane copolymer or a combination of the two mineral oil defoamers; the wetting agent is a polyether siloxane copolymer, a polyether modified siloxane or a combination of the two silicone twin structure surfactants; the leveling agent is a combination of the two polyacrylate, polyurethane or silicone leveling agents; the thickener is a combination of the two polyurethane or polyacrylate thickeners.
[0015] Furthermore, the alkaline regulator is one or more of ammonia water, ethanolamine, and ethylenediamine, and the pH of the coating is 8.5-9.5.
[0016] The method for preparing the coating of the present invention is carried out according to the following contents:
[0017] (1) 1 to 10 parts by weight of heavy calcium carbonate are sieved through a 100 to 600 mesh sieve, mixed with water, and then ground until the average particle size is less than 6 μm, and 0.5 to 1.5% of zinc sulfate and 1 to 1.5% of magnesium silicate are added to the heavy calcium carbonate, and stirred evenly to obtain a heavy calcium carbonate slurry, and 1 to 10 parts by weight of a calcium hydroxide solution is added and mixed evenly, and then 1 to 4% of glycerol is added and stirred evenly to obtain a mixed slurry; carbon dioxide is introduced for carbonization treatment until the pH of the reaction solution is 6 to 8, and nano-scale calcium carbonate is obtained; the mass fraction of the calcium hydroxide solution in the mixed slurry is 10 to 20%, and the mass fraction of the heavy calcium carbonate is 20 to 40%;
[0018] (2) mixing 3 to 8 parts by weight of titanium dioxide with the nano-scale calcium carbonate obtained in step (1), ball milling, adding 5 to 30 parts by weight of butyl titanate and 5 to 25 parts by weight of a mixed solution of oleic acid and sodium dodecylbenzene sulfonate, and reacting at a temperature of 50 to 70° C. for 1 to 5 hours to obtain a calcium carbonate-titanium dioxide composite material;
[0019] (3) 12 to 17 parts by weight of titanium dioxide, 10 to 20 parts by weight of aluminum oxide, 2 to 10 parts by weight of quartz sand, 5 to 10 parts by weight of barium sulfate, 2 to 10 parts by weight of rare earth silicate, 10 to 20 parts by weight of deionized water, and the calcium carbonate-titanium dioxide composite material of step (1) are sequentially added into a dispersion tank and uniformly dispersed to obtain a dispersion;
[0020] (4) placing the above dispersion in a high-speed oscillating grinder, and after grinding, the dispersion is led out and placed in a dispersion tank for further dispersion;
[0021] (5) adding 1 to 5 parts by weight of a coupling agent, 1 to 5 parts by weight of mica powder, 1 to 5 parts by weight of talc powder and 1 to 5 parts by weight of zinc phosphate to the dispersion of step (4) and continuing to disperse for 30 to 60 minutes;
[0022] (6) Add 20 to 30 parts by weight of water-based silicone acrylic resin and 0.5 to 1 part by weight of alkaline regulator into the above dispersion tank, and after dispersion, obtain the bridge concrete cooling coating.
[0023] Furthermore, the carbon dioxide flow rate in the carbonization treatment in step (1) is 50-150 L / h, and the volume concentration of carbon dioxide is 25%-35%.
[0024] Furthermore, the mass ratio of oleic acid to sodium dodecylbenzenesulfonate is 1 to 5:1.
[0025] The coating prepared by the method of the present invention has high solar reflectivity and radiation cooling function, can reflect more than 94% of solar radiation heat, and its surface heat can be continuously transferred to the cold source in outer space through the atmospheric window band (8-13μm), realizing the function of active surface radiation cooling. At the same time, the coating has good waterproof performance and can play an excellent maintenance role on bridge concrete.
[0026] The present invention aims at the problem that the composite titanium dioxide, especially the composite titanium dioxide prepared by combining titanium dioxide and calcium carbonate, has poor ultraviolet reflection effect. An improved calcium carbonate structure is proposed. The structure of calcium carbonate is regulated by a regulating agent, and butyl titanate is combined with a solvent to form a coating layer on the surface of calcium carbonate, thereby enhancing its weather resistance. The composite titanium dioxide finally prepared has improved ultraviolet reflection ability and weather resistance.
[0027] Compared with the existing known technologies, the technical solution provided by the present invention has the following significant effects:
[0028] (1) The bridge concrete cooling coating prepared by the present invention reflects more than 94% of the full-band energy of sunlight, which can prevent the concrete surface temperature from being too high due to solar radiation in summer.
[0029] (2) The bridge concrete cooling coating prepared by the present invention has the function of radiating infrared rays, which can emit the heat on the coating surface in the form of infrared rays through the atmospheric window (8-13 μm) to outer space. Coating it on the concrete surface can reduce the surface temperature of the concrete and prevent the occurrence of cracks, settlement and other problems caused by shrinkage stress due to excessive internal temperature gradient.
[0030] (3) The bridge concrete cooling coating prepared by the present invention has excellent waterproof performance, and its water resistance exceeds 960h. DETAILED DESCRIPTION
[0031] In order to make the objectives, technical solutions and advantages of the embodiments of the present invention more clearly understood, the spirit of the contents disclosed by the present invention will be described in detail below. After understanding the embodiments of the contents of the present invention, any technician in the relevant technical field can change and modify them according to the techniques taught by the contents of the present invention without departing from the spirit and scope of the contents of the present invention.
[0032] The exemplary embodiments of the present invention and the description thereof are used to explain the present invention but are not intended to limit the present invention.
[0033] Example 1
[0034] A method for preparing a bridge concrete cooling coating in this embodiment is carried out according to the following contents:
[0035] (1) 10 g of heavy calcium carbonate is sieved through a 500-mesh sieve, mixed with water, and then ground until the average particle size is less than 3 μm, and 1.2% of zinc sulfate and 1.2% of magnesium silicate are added to the heavy calcium carbonate, and stirred evenly to obtain a heavy calcium carbonate slurry, 10 g of calcium hydroxide solution is added and mixed evenly, and then 2% of glycerol is added and stirred evenly to obtain a mixed slurry; carbon dioxide (the carbon dioxide flow rate is 150 L / h, and the volume concentration of carbon dioxide is about 35%) is introduced for carbonization treatment, and the pH of the reaction solution is 6 to 8, thereby obtaining nano-scale calcium carbonate; the mass fraction of the calcium hydroxide solution in the mixed slurry is 12.5%, and the mass fraction of the heavy calcium carbonate is 25%;
[0036] (2) mixing 3 g of rutile titanium dioxide with the nano-scale calcium carbonate obtained in step (1), ball milling, adding 12 g of butyl titanate, 8 g of oleic acid and 2 g of sodium dodecylbenzene sulfonate, and reacting at a temperature of about 60° C. for 3 h to obtain a calcium carbonate-titanium dioxide composite material;
[0037] (3) 12 g of rutile titanium dioxide, 20 g of aluminum oxide, 7 g of quartz sand, 5 g of barium sulfate, 3 g of lanthanum yttrium silicate, 7 g of deionized water and the calcium carbonate-titanium dioxide composite material of step (1) are sequentially placed in a dispersion tank and dispersed at a uniform speed of 1000 r / min for 30 to 60 min; the above dispersion is placed in a high-speed vibration grinder, ground at a speed of 4000 r / min for 60 min, and then the dispersion is taken out and placed in a dispersion tank, and dispersed at 1000 r / min for another 30 min;
[0038] (4) Take 2.0g of polyurethane dispersant, 0.3g of silicone oil defoaming agent, 0.3g of polyether siloxane active agent, 0.2g of polyacrylate leveling agent, 3g of mica powder, 3g of talcum powder and 2g of zinc phosphate and add them to the above dispersion tank in sequence, increase the speed to 2000r / min and disperse at a uniform speed for 20min; increase the speed to 3000r / min, slowly add 1.2g of alkali swelling thickener to the above dispersion tank, and disperse at a uniform speed for 60min; add 25g of water-based silane resin and 1g of dimethylethanolamine to the above dispersion tank, and continue to disperse at 1000r / min for 30min to obtain bridge concrete cooling paint.
[0039] Example 2
[0040] (1) 10 g of heavy calcium carbonate is sieved through a 500-mesh sieve, mixed with water, and then ground until the average particle size is less than 3 μm, and 1.2% of zinc sulfate and 1.5% of magnesium silicate are added to the heavy calcium carbonate, and stirred evenly to obtain a heavy calcium carbonate slurry, 10 g of calcium hydroxide solution is added and mixed evenly, and then 2% of glycerol is added and stirred evenly to obtain a mixed slurry; carbon dioxide (the carbon dioxide flow rate is 150 L / h, and the volume concentration of carbon dioxide is about 35%) is introduced for carbonization treatment, and the pH of the reaction solution is 6 to 8, so as to obtain nano-scale calcium carbonate; the mass fraction of the calcium hydroxide solution in the mixed slurry is 12.5%, and the mass fraction of the heavy calcium carbonate is 30%;
[0041] (2) mixing 5 g of rutile titanium dioxide with the nano-scale calcium carbonate obtained in step (1), ball milling, adding 12 g of butyl titanate, 8 g of oleic acid and 2 g of sodium dodecylbenzene sulfonate, and reacting at a temperature of about 60° C. for 3 h to obtain a calcium carbonate-titanium dioxide composite material;
[0042] (3) 15 g of rutile titanium dioxide, 15 g of aluminum oxide, 5 g of quartz sand, 10 g of barium sulfate, 5 g of lanthanum yttrium silicate, 8 g of deionized water and the calcium carbonate-titanium dioxide composite material of step (1) are sequentially placed in a dispersion tank and dispersed at a uniform speed of 1000 r / min for 30 to 60 min; the above dispersion is placed in a high-speed vibration grinder, ground at a speed of 4000 r / min for 60 min, and then the dispersion is taken out and placed in a dispersion tank, and dispersed at 1000 r / min for another 30 min;
[0043] (4) Take 2.0g of polyurethane dispersant, 0.3g of silicone oil defoaming agent, 0.3g of polyether siloxane active agent, 0.2g of polyacrylate leveling agent, 2g of mica powder, 2g of talcum powder and 3g of zinc phosphate and add them to the above dispersion tank in sequence, increase the speed to 2000r / min and disperse at a uniform speed for 20min; increase the speed to 3000r / min, slowly add 1.2g of alkali swelling thickener to the above dispersion tank, and disperse at a uniform speed for 60min; add 25g of water-based silane resin and 1g of dimethylethanolamine to the above dispersion tank, and continue to disperse at 1000r / min for 30min to obtain bridge concrete cooling paint.
[0044] Example 3
[0045] (1) 10 g of heavy calcium carbonate is sieved through a 500-mesh sieve, mixed with water, and then ground until the average particle size is less than 3 μm, and 1.2% of zinc sulfate and 1.5% of magnesium silicate are added to the heavy calcium carbonate, and stirred evenly to obtain a heavy calcium carbonate slurry, 10 g of calcium hydroxide solution is added and mixed evenly, and then 2% of glycerol is added and stirred evenly to obtain a mixed slurry; carbon dioxide (the carbon dioxide flow rate is 150 L / h, and the volume concentration of carbon dioxide is about 35%) is introduced for carbonization treatment, and the pH of the reaction solution is 6 to 8, thereby obtaining nano-scale calcium carbonate; the mass fraction of the calcium hydroxide solution in the mixed slurry is 12.5%, and the mass fraction of the heavy calcium carbonate is 35%;
[0046] (2) mixing 8 g of rutile titanium dioxide with the nano-scale calcium carbonate obtained in step (1), ball milling, adding 15 g of butyl titanate, 9 g of oleic acid and 3 g of sodium dodecylbenzene sulfonate, and reacting at a temperature of about 60° C. for 2 h to obtain a calcium carbonate-titanium dioxide composite material;
[0047] (3) 12 g of rutile titanium dioxide, 20 g of aluminum oxide, 6 g of quartz sand, 20 g of barium sulfate, 4 g of lanthanum yttrium silicate, 10 g of deionized water and the calcium carbonate-titanium dioxide composite material of step (1) are sequentially placed in a dispersion tank and dispersed at a uniform speed of 1000 r / min for 30 to 60 min; the above dispersion is placed in a high-speed oscillating grinder, ground at a speed of 4000 r / min for 60 min, and then the dispersion is taken out and placed in a dispersion tank, and dispersed at 1000 r / min for another 30 min;
[0048] (4) Take 2.0g of polyurethane dispersant, 0.3g of silicone oil defoaming agent, 0.3g of polyether siloxane active agent, 0.2g of polyacrylate leveling agent, 1g of mica powder, 2g of talcum powder and 2g of zinc phosphate and add them to the above dispersion tank in sequence, increase the speed to 2000r / min and disperse at a uniform speed for 20min; increase the speed to 3000r / min, slowly add 1.2g of alkali swelling thickener to the above dispersion tank, and disperse at a uniform speed for 60min; add 20g of water-based silane resin and 1g of dimethylethanolamine to the above dispersion tank, and continue to disperse at 1000r / min for 30min to obtain bridge concrete cooling paint.
[0049] Comparative Example 1
[0050] The difference from Example 3 is that steps (1) and (2) are omitted, and the amount of titanium dioxide added is 20 g. The rest is the same as Example 3.
[0051] Comparative Example 2
[0052] The difference from Example 3 is that in step (1), magnesium silicate is replaced by sodium silicate. The rest is the same as Example 3.
[0053] Comparative Example 3
[0054] The difference from Example 3 is that glycerol is not added in step (1). The rest is the same as Example 3.
[0055] Comparative Example 4
[0056] The difference from Example 3 is that in step (1), magnesium silicate is replaced by sodium silicate, and glycerol is not added. The rest is the same as Example 3.
[0057] Comparative Example 5
[0058] The difference from Example 3 is that in step (2), sodium dodecylbenzene sulfonate is replaced by titanate and borate, and the titanate and borate are added in equal proportions. The rest is the same as Example 3.
[0059] Comparative Example 6
[0060] The difference from Example 3 is that: in step (1), 1.2% of zinc sulfate and 1.2% of magnesium silicate are added to 20g of calcium hydroxide solution, and after stirring, 2% of glycerol is added and stirred to obtain a mixed slurry; carbon dioxide (the flow rate of carbon dioxide is 150L / h, and the volume concentration of carbon dioxide is about 35%) is introduced for carbonization treatment, and the pH of the reaction liquid is 6-8 to obtain nano-scale calcium carbonate; the mass fraction of the calcium hydroxide solution in the mixed slurry is 12.5%. The rest is the same as Example 3.
[0061] Comparative Example 7
[0062] The difference from Example 3 is that the mass fraction of heavy calcium carbonate in step (1) is 15%. The rest is the same as Example 3.
[0063] The coatings prepared in the above examples and comparative examples were coated on a simulated bridge concrete surface (coating thickness 300-500 μm) and their performance was tested. The results are shown in Tables 1 and 2.
[0064] Table 1
[0065]
[0066]
[0067] Table 2
[0068]
[0069] By comparing the data in Table 1 and Table 2, it can be seen that the performance of the comparative examples is reduced in different situations when the preparation process of the calcium carbonate composite titanium dioxide is changed. Under the process conditions of the calcium carbonate composite titanium dioxide, the ultraviolet reflectivity of the comparative example 1 is significantly reduced compared with the embodiment, and its anti-aging performance is also significantly inferior to the embodiment in the artificial accelerated aging test. The comparative example 1 is compared with the embodiment and analyzed. The preparation process of the calcium carbonate composite titanium dioxide of the present invention can also improve the mechanical strength of the coating. According to comparative examples 2 to 4, the change of the regulating agent in the calcium carbonate preparation process also has a significant effect on the performance of the coating. After investigating the heavy calcium carbonate in comparative examples 4 and 7, it can also be seen that there is a certain effect on the performance of the coating.
[0070] The temperature of the embodiments and comparative examples was investigated: in sunny weather, from 10 a.m. to 1 p.m., after outdoor sunlight exposure, the temperature of the coatings of the embodiments and comparative examples and the temperature of the control group (not coated with the coating) are shown in Table 3.
[0071] Table 3
[0072]
[0073]
Claims
1. A bridge concrete cooling coating, characterized in that The invention is composed of 20-30 parts of water-based silicone-acrylic resin, 10-20 parts of titanium dioxide, 10-20 parts of aluminum oxide, 5-10 parts of barium sulfate, 2-10 parts of rare earth silicate, 1-10 parts of heavy calcium carbonate, 1-10 parts of calcium hydroxide, 0.01-2 parts of calcium carbonate regulator, 2-10 parts of quartz sand, 1-5 parts of mica powder, 1-5 parts of talc powder, 1-5 parts of zinc phosphate, 1-5 parts of auxiliary agent, 0.5-1 parts of alkaline regulator and 10-20 parts of deionized water in parts by weight. The calcium carbonate control agent is composed of zinc sulfate, magnesium silicate and glycerol in a mass ratio of 1:1-5:1-10.
2. The coating according to claim 1, characterized in that The water-based silicone-acrylic resin is one of the copolymer emulsions modified by organic silicon oxide and acrylate, and the diameter of the solid particles thereof is 100-500nm.
3. The coating according to claim 1, characterized in that The titanium dioxide is rutile titanium dioxide with a particle size of 250 to 800 nm.
4. The coating according to claim 1, characterized in that The rare earth silicate is one or more of zirconium yttrium silicate, lanthanum yttrium silicate, yttrium cerium silicate, zirconium lanthanum silicate, yttrium silicate, ytterbium silicate, cerium silicate, gadolinium silicate, samarium silicate, erbium silicate and holmium silicate.
5. The coating according to claim 1, characterized in that The auxiliary agents are dispersants, defoamers, wetting agents, leveling agents and thickeners; the dispersants are one or a combination of a high molecular weight block copolymer solution containing pigment affinity groups or an aqueous solution containing a polymer with high pigment affinity groups and a surfactant; the defoamers are one or a combination of a polyether siloxane copolymer or a mineral oil defoamer.
6. The coating according to claim 1, characterized in that The wetting agent is one or a combination of polyether siloxane copolymer, polyether modified siloxane or silicone twin structure surfactant; the leveling agent is one or a combination of polyacrylate, polyurethane or silicone leveling agents; the thickener is one or a combination of polyurethane or polyacrylate thickeners.
7. The coating according to claim 1, characterized in that The alkaline regulator is one or more of ammonia water, ethanolamine and ethylenediamine, and the pH value of the coating is 8.5-9.
5.
8. A method for preparing the coating according to claim 1, characterized in that The preparation method is carried out according to the following contents: (1) 1 to 10 parts by weight of heavy calcium carbonate are sieved through a 100 to 600 mesh sieve, mixed with water, and then ground until the average particle size is less than 6 μm, and 0.5 to 1.5% of zinc sulfate and 1 to 1.5% of magnesium silicate are added to the heavy calcium carbonate, and stirred evenly to obtain a heavy calcium carbonate slurry, and 1 to 10 parts by weight of a calcium hydroxide solution is added and mixed evenly, and then 1 to 4% of glycerol is added and stirred evenly to obtain a mixed slurry; carbon dioxide is introduced for carbonization treatment until the pH of the reaction solution is 6 to 8, and nano-scale calcium carbonate is obtained; the mass fraction of the calcium hydroxide solution in the mixed slurry is 10 to 20%, and the mass fraction of the heavy calcium carbonate is 20 to 40%; (2) mixing 3 to 8 parts by weight of titanium dioxide with the nano-scale calcium carbonate obtained in step (1), ball milling, adding 5 to 30 parts by weight of butyl titanate and 5 to 25 parts by weight of a mixed solution of oleic acid and sodium dodecylbenzene sulfonate, and reacting at a temperature of 50 to 70° C. for 1 to 5 hours to obtain a calcium carbonate-titanium dioxide composite material; (3) 12 to 17 parts by weight of titanium dioxide, 10 to 20 parts by weight of aluminum oxide, 2 to 10 parts by weight of quartz sand, 5 to 10 parts by weight of barium sulfate, 2 to 10 parts by weight of rare earth silicate, 10 to 20 parts by weight of deionized water, and the calcium carbonate-titanium dioxide composite material of step (1) are sequentially added into a dispersion tank and uniformly dispersed to obtain a dispersion; (4) placing the above dispersion in a high-speed oscillating grinder, and after grinding, the dispersion is led out and placed in a dispersion tank for further dispersion; (5) adding 1 to 5 parts by weight of a coupling agent, 1 to 5 parts by weight of mica powder, 1 to 5 parts by weight of talc powder and 1 to 5 parts by weight of zinc phosphate to the dispersion of step (4) and continuing to disperse for 30 to 60 minutes; (6) Add 20 to 30 parts by weight of water-based silicone acrylic resin and 0.5 to 1 part by weight of alkaline regulator into the above dispersion tank, and after dispersion, obtain the bridge concrete cooling coating.
9. The preparation method according to claim 8, characterized in that The carbon dioxide flow rate in the carbonization treatment described in step (1) is 50-150 L / h, and the volume concentration of carbon dioxide is 25%-35%.
10. The preparation method according to claim 8, characterized in that The mass ratio of oleic acid to sodium dodecylbenzene sulfonate is 1 to 5:1.
Citation Information
Patent Citations
A kind of preparation method of the composite titanium dioxide of titanium coated light calcium carbonate
CN105778569B
A cooling and heat-insulating protective coating for concrete bridges
CN109593431B
Aqueous slurry of nano calcium carbonate as well as preparation method and application thereof
CN105883882A
Nano calcium carbonate powder water-based coating material and preparation method thereof
CN111961373A
Preparation method of nano calcium carbonate for PVC (polyvinyl chloride) edge band
CN114212812A
